Retraction Notice: Comparison of Chondroitin Sulfate-E Expression in Benign and Malignant Epithelial Type Ovarian Tumors - Kemala Isnainiasih Mantilidewi (Indonesian Journal of Obstetrics & Gynecology Science, 2025)
Summary:This article has been formally retracted and the PDF file withdrawn from the journal’s database at the request of the authors.Significant concerns were raised regarding the accuracy and reliability of the dataset, rendering the findings no longer robust or dependable for scientific use. Additionally, it was disclosed that the manuscript was submitted without the explicit consent of all listed co-authors.To preserve the integrity of the medical literature, the Editorial Board has removed the original content. This page remains as a permanent record of the retraction. A replacement notice has been issued in the original volume to inform readers of this retraction.We apologize for any inconvenience caused to our reviewers and readers.Readers are advised not to cite this article.